Faktor Internal Dan Eksternal Yang Mempengaruhi Kualitas Audit : Studi Kasus Pada Dinas Inspektorat Provinsi Sulawesi Barat - Dahlia Usman; Ratna Sari; Reza Ramdani (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2023)
This riset aims to analyze the influence of internal and external factors on audit quality, using a case study at the Inspectorate Office of West Sulawesi Province. The internal factors examined in this research are professional skepticism and auditor competence, while the external factor tested is the work environment. The population in this study includes all auditors and P2UPD personnel working at the Inspectorate Office of West Sulawesi Province. The sample was determined using a simple random sampling technique, consisting of 52 auditors and P2UPD. The data collection technique used in this study is a field research method. To gather field data, a survey method was applied by distributing questionnaires to 52 respondents. The data analysis in this quantitative approach involved descriptive statistical analysis, data quality tests, classical assumption tests, multiple linear regression analysis, coefficient of determination (R Square), F-test, and t-test. The data were processed and analyzed using the SPSS statistical software. The results of the data analysis show that partially, professional skepticism has a positive and significant effect on audit quality, competence has a positive and significant effect on audit quality, and the work environment also has a positive and significant effect on audit quality. Simultaneously, the three independent variables have a combined significant effect, indicating that improving audit quality can be achieved by enhancing auditor competence and professional skepticism, as well as improving the work environment at the Inspectorate Office.